Complex assessing of aridity in Ukraine - Zatula, Vasyl (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Introduction. The aridity is an important part of the climate characterization of a territory. Over the past 100 years, aridity indices have been used to assess it.The purpose of article is to characterize the patterns of the spatial distribution and changes over time of aridity indices on the territory of Ukraine for the period 1961-2020.Data and methods. The Pinna combinative index (PCI) and its modification (PCIm) were used to determine the aridity assessment. Basic calculations of these indices were performed for more than 150 weather stations in Ukraine over the last two 30-year periods. The main results of the research were obtained using statistical methods and GIS technologies.Results. It has been found that the use of the PCI index in temperate countries may be constrained by its high sensitivity to the moisture conditions in the driest month of the year, which often extends beyond the growing season. The modification of the index proposed by the author better reflects the peculiarities of aridity in temperate countries, which are necessary for making decisions on agricultural irrigation. Maps of the distribution of aridity indices for 1961-1990 and 1991-2020 periods and its changes between them are presented. For the modified version of the index, an in-depth statistical analysis was conducted. It is shown that the aridity of Ukraine increases at least one and a half times faster with moving from north to south than with moving away from the Atlantic Ocean in the eastern direction. The tendency to increase the humidity of the climate with elevation turned out to be particularly clear (the coefficient of determination ). The coefficients of the linear trend of this indicator in both parts of the studied period are close to 6 units in terms of elevation per 100 m. Multiple regression models were shown that the leading role in the formation of the total variance of the index is played by absolute elevation (with a share of more than 60-65%) and geographic longitude (with a share of more than 20%). Changes in the PCIm index were observed in different regions of Ukraine with different signs. As a rule, they did not exceed 5 units, but the fact that this indicator exceeds one standard deviation (~2.5 units) already indicates a significant violation of previous climatic conditions. The calculated changes in the PCIm index in about half of the country's territory are actually on the verge of this criterion of irreversible climate change. Aridization of the climate is becoming an important signal of the imbalance of the regional climate system of Ukraine, and therefore requires an urgent response at the level of development and implementation of appropriate state climate policy measures.The scientific novelty. The paper analyses for the first time the limits of applicability of the Pinna combinative index and proposes and justifies its improvement.Practical significance. The proposed modification of Pinna combinative index can be of great importance for the comparability of climate aridity assessments in countries with temperate and subtropical climates. The assessment of the aridity in Ukraine will be useful in the development and implementation of state climate policy measures in areas of intensive climate aridization according to Sustainable Development Goals of United Nations.